The aqueous extract of the sage plant leaves - Sabaa O. Albalawi; Hala. A. Shaheed; Shirin S. Al-Shewaili (University of Thi-Qar Journal of agricultural research, 2025)
sage leaves were brought from local markets, the leaves were washed thoroughly and then dried well under the sun for three days, turning them continuous .from time to time to prevent rotting, the leaves were then ground using an electric grinder (Morter) and the powder was stored in clean plastic bags at room temperature until use, the aqueous abstract was Prepare according to the method of Hernandes et al. (1994), which involves. mixing a quantity of dried sage leaf powder with a quantity of distilled water in a ratio of 1 g: 2 ml of distilled water by placing it in a water bath at 60 °C for one hour, the solution was then left to stand for 24 hours at room. temperature, after which the resulting. mixture was filtered through several layers of sterile gauze; the concentrated. liquid was then ready.